2015
DOI: 10.4103/0976-500x.171883
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the clinical efficacy and safety of agomelatine with escitalopram in major depressive disorder patients: A randomized, parallel-group, phase IV study

Abstract: Objective:To compare the efficacy of agomelatine with escitalopram in the treatment of major depressive disorder (MDD), improve sleep in MDD patients and study the adverse effects of agomelatine.Materials and Methods:Randomized, parallel-group, open-label study. The primary efficacy outcome was change from baseline to last post-baseline value in Hamilton depression rating scale and Leeds sleep evaluation questionnaire scale. Both parametric and nonparametric tests were applied for analysis.Results:Within-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other studies have found significant differences in other sleep parameters (e.g. daytime sleepiness, shorter SoL) using questionnaires (Urade et al, 2015), but as our autistic adults with ID are nonverbal, questionnaires are not validated for our population. Studies in participants with mood disorders or anxiety that used subjective sleep measures have also reported an increase in TST following agomelatine treatment (Hale et al, 2010;Stein et al, 2008), and a reduction in insomnia symptoms has been observed upon agomelatine treatment (Lemoine et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have found significant differences in other sleep parameters (e.g. daytime sleepiness, shorter SoL) using questionnaires (Urade et al, 2015), but as our autistic adults with ID are nonverbal, questionnaires are not validated for our population. Studies in participants with mood disorders or anxiety that used subjective sleep measures have also reported an increase in TST following agomelatine treatment (Hale et al, 2010;Stein et al, 2008), and a reduction in insomnia symptoms has been observed upon agomelatine treatment (Lemoine et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…They found that escitalopram had superior antidepressant effects from 6 to 24 weeks and that, during the same period, agomelatine had superior effects on sleep outcomes. [ 1 ] We have important concerns about the design and methods of this study:…”
mentioning
confidence: 99%